RESPON PEMBERIAN AIR KELAPA DAN KOMPOS KULIT PISANG TERHADAP PERTUMBUHAN BAYAM HIJAU (Amaranthus tricolor L.) - Syah Yudi, Syah Yudi; Lestari, Widya; Putri Septyani, Ika Ayu; Harahap, Fitra Syawal (Agros Journal of Agriculture Science, 2024)
Green spinach (Amaranthus tricolor L.) has high nutritional value so efforts are needed to increase its production, one of which is providing good nutrition and growth regulators (ZPT) for plants. The aim of this research was to determine the effect of banana peel compost, the effect of coconut water ZPT, and the combination of banana peel and coconut water factors in increasing the growth of green spinach. This research was carried out from January 25 2024 to February 18 2024 located on Jln. Tapian Nauli No. 67, Bale Lake, Rantau Selatan District, Labuhanbatu Regency, North Sumatra. This research used a factorial randomized block design (RAK) consisting of 2 factors. Factor A (banana peel compost) includes P0: control, P1: 250g/plant, P2: 500g/plant and Factor B (coconut water zpt) includes A0: control, A1: 150ml/liter of water, A2: 300ml/liter of water, Each treatment was repeated 3 times to obtain 27 experimental units and analyzed using the ANOVA test at 5% and 1% levels followed by the Duncan 5% test. With research parameters, namely plant height, number of leaves, root length, and plant fresh weight. It is known from the research results that the provision of compost from banana peel waste and coconut water zpt has a significant effect on the height of plants in 1 week after planting (WAP), 2 WAP, and 3 WAP, the number of leaves in 1 WAP, 2 WAP, 3 WAP. Root length and wet weight of spinach with banana peel compost treatment 500g/plant and coconut water zpt 300ml/ liter of water showed the highest response. Key words : green spinach, banana peel compost, coconut water olc. INTISARIBayam hijau (Amaranthus tricolor L.) memiliki nilai gizi yang tinggi sehingga diperlukan upaya untuk meningkatkan produksinya, salah satunya adalah memberikan nutrisi dan zat pengatur tumbuh (zpt) yang baik bagi tanaman. Tujuan penelitian ini adalah untuk mengetahui pengaruh kompos kulit pisang, pengaruh zpt air kelapa, dan kombinasi faktor kulit pisang dan air kelapa dalam meningkatkan pertumbuhan bayam hijau. Penelitian ini dilaksanakan pada 25 Januari 2024 sampai dengan 18 Februari 2024 berlokasi di Jln. Tapian Nauli No. 67, Danau Bale, Kecamatan Rantau Selatan, Kabupaten Labuhanbatu, Sumatera Utara. Penelitian ini menggunakan rancangan acak kelompok (RAK) faktorial terdiri dari 2 faktor. Faktor A (kompos kulit pisang) meliputi P0 : kontrol, P1 : 250g/ tanaman, P2 : 500g/ tanaman dan Faktor B (zpt air kelapa) meliputi A0 : kontrol, A1 : 150ml/ liter air, A2 : 300ml/ liter air, masing-masing perlakuan diulang sebanyak 3 kali sehingga diperoleh 27 satuan percobaan dan dianalisis menggunakan uji anova taraf 5% dan 1% dilanjut dengan uji Duncan 5%. Dengan parameter penelitian, yaitu tinggi tanaman, jumlah daun, panjang akar, dan berat basah tanaman. Diketahui dari hasil penelitian bahwa pemberian kompos dari limbah kulit pisang dan zpt air kelapa berpengaruh nyata terhadap tinggi tanaman 1MST, 2MST, dan 3MST, jumlah daun 1MST, 2MST, 3MST. Panjang akar dan berat basah bayam dengan perlakuan kompos kulist pisang 500g/tanaman dan air kelapa 300ml/ liter air menunjukkan respon tertinggi. Kata kunci : bayam hijau, kompos kulit pisang, zpt air kelapa.